The lipid environment modulates cardiolipin and phospholipid constitution in wild type and tafazzin‐deficient cells. Issue 1 (28th September 2021) - Oemer, Gregor; Koch, Jakob; Wohlfarter, Yvonne; Lackner, Katharina; Gebert, Rita E. M.; Geley, Stephan; Zschocke, Johannes; Keller, Markus A.
Abstract: Deficiency of the transacylase tafazzin due to loss of function variants in the X‐chromosomal TAFAZZIN gene causes Barth syndrome (BTHS) with severe neonatal or infantile cardiomyopathy, neutropenia, myopathy, and short stature. The condition is characterized by drastic changes in the composition of cardiolipins, a mitochondria‐specific class of phospholipids. Studies examining the impact of tafazzin deficiency on the metabolism of other phospholipids have so far generated inhomogeneous and partly conflicting results. Recent studies showed that the cardiolipin composition in cells and different murine tissues is highly dependent on the surrounding lipid environment. In order to study the relevance of different lipid states and tafazzin function for cardiolipin and phospholipid homeostasis we conducted systematic modulation experiments in a CRISPR/Cas9 knock‐out model for BTHS. We found that—irrespective of tafazzin function—the composition of cardiolipins strongly depends on the nutritionally available lipid pool. Tafazzin deficiency causes a consistent shift towards cardiolipin species with more saturated and shorter acyl chains. Interestingly, the typical biochemical BTHS phenotype in phospholipid profiles of HEK 293T TAZ knock‐out cells strongly depends on the cellular lipid context. In response to altered nutritional lipid compositions, we measured more pronounced changes on phospholipids that were largely masked under standard cell culturing conditions, therewith giving a possible explanation for the conflicting results reported so far on BTHS lipid phenotypes. Abstract :